Perbandingan Sistem Jaminan Sosial Antara Indonesia Dan Malaysia Dalam Rangka Pemenuhan Hak Kesehatan Di Indonesia - Hayanti, Vivi; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
Everyone on this planet is worried about their health. It is explained in paragraph 25 (1) of the 1948 United Nations Declaration on the History of Humanity, which states that